2020
DOI: 10.1175/jpo-d-19-0154.1
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Rates and Bottom Drag in Bering Strait

Abstract: Three shipboard survey lines were occupied in Bering Strait during autumn of 2015, where high-resolution measurements of temperature, salinity, velocity, and turbulent dissipation rates were collected. These first-reported turbulence measurements in Bering Strait show that dissipation rates here are high even during calm winds. High turbulence in the strait has important implications for the modification of water properties during transit from the Pacific Ocean to the Arctic Ocean. Measured diffusivities avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…If we force a linear relation in panel (a), we find a drag coefficient of C d = 8.2×10 −4 . This value is comparable to but smaller than the typical range of bottom drag values of (1-3) × 10 −3 and the bottom drag deduced from in situ observations in Bering Strait of 2.3 × 10 −3 (Couto et al, 2020). The red data points in Fig.…”
Section: Tidal Mixingsupporting
confidence: 51%
See 3 more Smart Citations
“…If we force a linear relation in panel (a), we find a drag coefficient of C d = 8.2×10 −4 . This value is comparable to but smaller than the typical range of bottom drag values of (1-3) × 10 −3 and the bottom drag deduced from in situ observations in Bering Strait of 2.3 × 10 −3 (Couto et al, 2020). The red data points in Fig.…”
Section: Tidal Mixingsupporting
confidence: 51%
“…Heat loss resulting from vertical heat fluxes contributes to the heat loss to the atmosphere and to the deep ocean, but not to the lateral heat loss. Several processes can lead to lateral heat loss north of Svalbard, including eddy spreading from the slope into the basin (Crews et al, 2018;Våge et al, 2016). Using eddy-resolving regional model results, Crews et al (2018) found that eddies export 1.0 TW out of the boundary current, delivering heat into the interior Arctic Ocean at an average rate of ∼ 15 W m −2 .…”
Section: Atlantic Water Heat Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, however, our method is different from Dewey and Crawford (1988). We determine the values of u ⋆ using a least-squares fit to ɛ, similar to Couto et al (2020).…”
Section: Friction Velocity Estimatesmentioning
confidence: 99%